Microglial activation correlates in vivo with both tau and amyloid in Alzheimer's disease - Dani, Melanie; Wood, Melanie; Mizoguchi, Ruth; Fan, Zhen; Walker, Zuzana; Morgan, Richard; Hinz, Rainer; Biju, Maya; Kuruvilla, Tarun; Brooks, David J; Edison, Paul (Brain (London, England : 1878), 2018)
The relationship between microglial activation and protein aggregation in Alzheimer's disease is still debated. Dani et al. report that in vivo microglial activation strongly correlates with tau aggregation and amyloid deposition in both mild cognitive impairment and Alzheimer's disease. Any future therapy or prevention should target all three processes. Abstract Alzheimer's disease is characterized by the histopathological presence of amyloid-β plaques and tau-containing neurofibrillary tangles. Microglial activation is also a recognized pathological component. The relationship between microglial activation and protein aggregation is still debated. We investigated the relationship between amyloid plaques, tau tangles and activated microglia using PET imaging. Fifty-one subjects (19 healthy controls, 16 mild cognitive impairment and 16 Alzheimer's disease subjects) participated in the study. All subjects had neuropsychometric testing, MRI, amyloid (18F-flutemetamol), and microglial (11C-PBR28) PET. All subjects with mild cognitive impairment and Alzheimer's disease and eight of the controls had tau (18F-AV1451) PET. 11C-PBR28 PET was analysed using Logan graphical analysis with an arterial plasma input function, while 18F-flutemetamol and 18F-AV1451 PET were analysed as target:cerebellar ratios to create parametric standardized uptake value ratio maps. Biological parametric mapping in the Statistical Parametric Mapping platform was used to examine correlations between uptake of tracers at a voxel-level. There were significant widespread clusters of positive correlation between levels of microglial activation and tau aggregation in both the mild cognitive impairment (amyloid-positive and amyloid-negative) and Alzheimer's disease subjects. The correlations were stronger in Alzheimer's disease than in mild cognitive impairment, suggesting that these pathologies increase together as disease progresses. Levels of microglial activation and amyloid deposition were also correlated, although in a different spatial distribution; correlations were stronger in mild cognitive impairment than Alzheimer's subjects, in line with a plateauing of amyloid load with disease progression. Clusters of positive correlations between microglial activation and protein aggregation often targeted similar areas of association cortex, indicating that all three processes are present in specific vulnerable brain areas. For the first time using PET imaging, we show that microglial activation can correlate with both tau aggregation and amyloid deposition. This confirms the complex relationship between these processes. These results suggest that preventative treatment for Alzheimer's disease should target all three processes.